2018
DOI: 10.1186/s40543-018-0146-0
|View full text |Cite
|
Sign up to set email alerts
|

Cytotoxicity evaluation of a Thai herb using tetrazolium (MTT) and sulforhodamine B (SRB) assays

Abstract: Background: Various assays are used to evaluate the cytotoxic effect of chemicals on cultured cells. The sulforhodamine B (SRB) colorimetric assay is based on the ability of the SRB dye to bind basic amino acid residues on proteins. In contrast, the MTT (dimethylthiazol-diphenyltetrazolium bromide) colorimetric assay is based on mitochondrial uptake and succinate dehydrogenase reduction of soluble, yellow, MTT tetrazolium salt to an insoluble blue MTT formazan product. The aim of this study was to evaluate the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
66
1
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 103 publications
(69 citation statements)
references
References 16 publications
(14 reference statements)
0
66
1
2
Order By: Relevance
“…In the SRB assay, the dye binds to basic amino acids of cellular proteins and cell density determination refers to total protein mass . While, tetrazolium (MTT) technique depended upon mitochondrial dehydrogenase enzyme in which these enzymes can reduce the tetrazolium dye to its insoluble formazan with a purple color …”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…In the SRB assay, the dye binds to basic amino acids of cellular proteins and cell density determination refers to total protein mass . While, tetrazolium (MTT) technique depended upon mitochondrial dehydrogenase enzyme in which these enzymes can reduce the tetrazolium dye to its insoluble formazan with a purple color …”
Section: Resultsmentioning
confidence: 99%
“…found that isonicotinic acid hydrazide, owing hydrazide moiety, cause human hepatoblastoma cell line (HepG2), healthy cell, injury by mitochondrial DNA damage . In addition to, MTT is based on mitochondrial uptake . From all the previous reasoning, it can be easily explained the difference between the obtained results from two assays.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations